2001
DOI: 10.1016/s0007-8506(07)62995-3
|View full text |Cite
|
Sign up to set email alerts
|

Task Specific Uncertainty in Coordinate Measurement

Abstract: Task specific uncertainty is the measurement uncertainty associated with the measurement of a specific feature using a specific measurement plan. This paper surveys techniques developed to model and estimate task specific uncertainty for coordinate measuring systems, primarily coordinate measuring machines using contacting probes. Sources of uncertainty are also reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
88
0
6

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(94 citation statements)
references
References 66 publications
(72 reference statements)
0
88
0
6
Order By: Relevance
“…According to Taylor and Kuyatt [4] measurement outcome should include a quantitative statement of its uncertainty for completeness and valid judgment of final results. When measurement uncertainty is associated with measurement of particular feature using specific measurement plan, it is known as task specific uncertainty [5]. Task specific uncertainty depends on number of factors such as sampling strategies, measuring object, probing technique, environmental conditions, evaluation software, measuring equipment, etc.…”
Section: Measurement Uncertainties Associated With Cmmmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Taylor and Kuyatt [4] measurement outcome should include a quantitative statement of its uncertainty for completeness and valid judgment of final results. When measurement uncertainty is associated with measurement of particular feature using specific measurement plan, it is known as task specific uncertainty [5]. Task specific uncertainty depends on number of factors such as sampling strategies, measuring object, probing technique, environmental conditions, evaluation software, measuring equipment, etc.…”
Section: Measurement Uncertainties Associated With Cmmmentioning
confidence: 99%
“…For instance, work of Weckenmann et al [6], where contributions of different uncertainties have been identified on CMM measurement results through measurement of car body. A comprehensive review of techniques in which Wilhelm et al [5] estimated task specific uncertainty for CMMs represent significant contribution in this area. Butler [9] identified measuring probe as one of the most important sources of error in CMM measurement results.…”
Section: Measurement Uncertainties Associated With Cmmmentioning
confidence: 99%
“…In the case study, coordinate measuring machines dominate the system of measurement, and experiments are carried out on the same machines that will be used in production to evaluate their capability; simulation of measurement capability is rarely used within an industrial context [28]. However, these experiments cannot be performed until prototypes have been manufactured, and the results cannot easily be generalised because they are highly sensitive to the measuring task [29]. It is therefore difficult to know whether a design change is likely to challenge the measurement system, even when employing the same technology.…”
Section: -Knowing What To Reusementioning
confidence: 99%
“…Several methods for determining the measurement uncertainty of a specific measurement task were described in the review paper [4]. Some of these methods are documented in the ISO 15530 series of standards: the use of multiple strategy measurements without calibrated workpiece 15530-2 (deleted), the use of calibrated workpieces or standards 15530-3 [5], and the use of computer simulation 15530-4 [6].…”
Section: Introductionmentioning
confidence: 99%